THE EFFECTIVITY OF CYSTEAMINE SUPPLEMENTATION ON IMPROVING THE IN VITRO FERTILIZATION RATE OF SHEEP OOCYTES - Dona Astari Nurkarimah; Ekayanti Mulyawati Kaiin; Ni Wayan Kurniani Karja; Mohamad Agus Setiadi (Jurnal Kedokteran Hewan, 2021)
The purpose of this study was to evaluate the effectiveness of cysteamine supplementation on the maturation medium and/or in vitro fertilization medium with regards to improving the normal fertilization rate of sheep oocytes, which are characterized by the formation of two pronuclei. Grade A and B oocytes were matured in medium-199 with 0.3% bovine serum albumin (BSA), 10 IU/mL follicle stimulating hormone (FSH), 10 IU/mL human chorionic gonadotrophin (hCG), and 50 μg/mL gentamicin added for 24 hours in a 5% CO2 incubator at 39° C. The treatment group was divided into the following groups: a control group with no cysteamine (P1), a group with 100 μM cysteamine in the maturation medium (P2), a group with 100 μM cysteamine in the fertilization medium (P3), and a group with 100 μM cysteamine both in the maturation and fertilization medium (P4). The fertilization was carried out by incubating sperm-oocytes for 12 hours and then staining them with 1% aceto-orcein to observe the formation of a pronucleus. Normal fertilization rates obtained by each treatment group were 56.5% (P1), 57.1% (P2), 57.8% (P3), and 59.9% (P4) with no significant difference (P0.05) between groups. It was concluded that 100 μM cysteamine supplementation in both the maturation medium and fertilization medium was not able to increase the normal fertilization rate of sheep oocytes.